ON THE “IRRATIONAL” IN POLITICAL SCIENCE AND IN POLITICAL PRACTICES - Boris F. Martynov (Сравнительная политика, 2018)
The author, parting from the premise that the world political analysts failed to foresee some prominent political changes of the recent times, comes to the conclusion about the inadequacy of the existing methods of political analysis and forecasting. Some recent scientifi c works by Russian and foreign specialists made him think that a purely rationalist approach to the world studies, that has been used since the times of the Renascence, partly exhausted itself. Along with the Russian authors Baranovski and Bogaturov, the Author thinks, that from now on our political analysis should be enriched by the introduction of some elements of a so called “natural – chaotic essence”, which infl uences the world events through the element of “happening”. The core of such an approach could include: 1) the recognition of a partial inadequacy of purely rationalist methods in our assessment of human nature and social phenomena; 2) the transference of the center of gravity in our social studies from economic to national-ethnic, culturological and civilizational aspects; 3) a wider use of historic analogies in the studies of all the problems of modern international relations. A linear character of our political forecasting will most evidently suffer because of that. Nevertheless, it would contribute to the elaboration of a more stereoscopic, complex view on the international relations as a whole and, particularly, on such problems as terrorism, illegal migration, separatism, and so on. The Author agrees with the thesis of some Occidental analysts (Bernard Yak, e.g.) that we should learn to “dutifully live” with certain irrational phenomena of political life (e.g. – nationalism), by purposely searching for and the accentuation of their “brighter” sides in the detriment of “dark” ones. The main prerequisite of such an accentuation, according to the Author, should be a wider use of education and culture. Culture, as a “positive” irrational actor (in all its demonstrations, including the political culture) should be seen as a promoter of a more active information strategy of Russia in the world arena. A shift for such a strategy is utterly necessary because a continuation of a “defensive” policy in this sphere can lead to signifi cant losses.